The effect of hydrothermal alteration on the Sr and Nd isotopic signatures of the Barra do Itapirapua Carbonatite, Southern Brazil - Andrade, FRD; Moller, P.; Hohndorf, A. (Univ Chicago Press, 1999)
The Cretaceous Barra do Itapirapua carbonatite in southern Brazil experienced extensive postmagmatic hydrothermal alteration. In this article, Sr and Nd isotope ratios of coexisting samples of hydrothermally overprinted and of preserved, nonoverprinted carbonatite are presented. Hydrothermal alteration caused strong REE enrichment, leading to the formation of minerals of the bastnaesite group. In the overprinted carbonatite, Nd contents reach 4000 ppm, two orders of magnitude higher than in the fresh carbonatite, but epsilon(Nd) varies only within a range of 3.4 units. In contrast, Sr was leached from the carbonatite during the postmagmatic alteration; hence values of around 10,000 ppm in the fresh carbonatite drop to about 1000 ppm in the overprinted samples. Leaching is accompanied by a variation of Sr isotopic composition toward more radiogenic values, resulting in an increase of 15 units in epsilon(Sr). Variation of Sr isotopic composition is related to postmagmatic alteration and is decoupled from the variation of Nd isotopic composition, ruling out heterogeneities in the mantle source as the main cause of isotopic variability in the data set. Furthermore, this cannot be explained by bulk crustal contamination. A two-step model is proposed in which (1) a REE-rich, carbonatite-derived hydrothermal fluid overprinted the pristine carbonatite, causing REE-enrichment with a relative small change of isotopic composition; and (2) crust-derived hydrothermal fluids percolated the cooling carbonatite, leaching the original Sr from the carbonatite and introducing a more radiogenic Sr isotopic signature. The amounts of carbonatite-derived Nd with primitive, carbonatite-like Nd isotope ratios introduced during the first stage of hydrothermal alteration are high enough to buffer the effect of crust-derived Nd on the Nd isotopic composition of the overprinted carbonatite.